Construction of training process of skiers-racing drivers to the competitions on skiatlon - Sidorova T.V; Kotlyar S.N; Bizin V.P (Kharkov National Pedagogical University, 2012)
The state of method of preparation of skiers-racing drivers is considered to participating in races classic and skating styles of movement. 30 skilled sportsmen took part in an experiment. 60 leading trainers and skilled sportsmen took part in the questionnaire questioning. Certainly, that with introduction of skiatlon the method of preparation of sportsmen changed to the program of competitions. The factor analysis of indexes which influence on a sporting result is rotined. The contribution of different constituents is set to the sporting result. Model descriptions of sportsmen which allow to show high results in races in skiatlon are developed. It is set that on pattens considerable differences have classic and skating style of movement in all of kinematics and dynamic descriptions. The anthropometric models of skilled skiers-racing drivers, which successfully come forward in competitions different styles of movement on pattens, are set.